Learning Rangguk Dance at Puti Sekanti Cultural Studio in the Context of cultural participation - Frizia Nuary Novalia, Frizia Nuary Novalia; Malarsih Malarsih; Eko Sugiarto (Universitas Negeri Semarang, 2025)
Culture develops and is standardized in tradition in the form of art. art has a strong cultural philosophy that reflects the identity of the local community. One of the arts is rangguk dance which has its own uniqueness and has meaning in each form. The phenomenon that occurs at this time the development of rangguk dance is less attractive through this research the problem focused on how the process of learning rangguk dance to maintain local culture and the participation of the role of the studio through the learning process. The method used is qualitative method with data collection techniques of interviews, observation and documentation. The results of research on the context of cultural participation of rangguk dance in the puti sekanti cultural studio, there is a teaching and learning process through the non-formal education system in learning cultural traditions in the puti sekanti studio. The role of the puti sekanti sangar in preserving rangguk dance through a structured learning program in which there is a final evaluation process by demonstrating the dance, students are made in groups to measure understanding of the material about rangguk dance. Thus, the puti sekanti cultural studio instills the essence of their role in carrying out the obligation to love, inherit and preserve traditional dance, this reflects the puti sekanti studio in maintaining cultural heritage